Impact of different water activities (aw) adjusted by solutes on high pressure high temperature inactivation of Bacillus amyloliquefaciens spores - Sevenich, Robert; Reineke, Kai; Hecht, Philipp; Fröhling, Antje; Rauh, Cornelia; Schlüter, Oliver; Knorr, Dietrich (Frontiers in Microbiology, 2015)
Much research has been conducted to comprehend the mechanisms of high pressure (HP) inactivation of spores in aqueous systems but for food model systems these information are scarce. In these systems spores can interact with ingredients which could lead to retarded inactivation, which can cause a problem for the sterilization process. The protective mechanism of a reduced a_W-value is still unclear. HP processing might prove valuable to overcome protective effects of solutes and achieve shorter process times for sterilization under HP. To gain insight into the underlying mechanisms five a_W-values (0.9, 0.92, 0.94, 0.96, 1) were adjusted with 2 different solutes (NaCl, sucrose). Solutions were inoculated with spores of Bacillus amyloliquefaciens and treated at 105,110°C and115°C at 600 MPa. A thermal inactivation was conducted at the same temperatures for a compraison with the high pressure data. The influence of high pressure high temperature treatment on the inactivation, the DPA-release and membrane constitution was assessed by plate count, HPLC and flow cytometry. The results show that during HP treatments sucrose and salt both have a protective effect, in which the influence of sucrose on the retarded inactivation is higher. The threshold aw, which is 0.94, here salt and sucrose have a significant influence on the inactivation. The comparison of thermal (105-115°C) and high pressure and high temperature (600 MPa, 105-115°C) treated samples showed that the time needed to achieve a 4-5 log inactivation can be reduced at 600 MPa.The release of dipicolinic acid (DPA) is the rate limiting step of the inactivation and therefore monitoring the release is of great interest. The DPA-release is slowed is slowed down in high concentrated solutions (e.g. sucrose, salt) in comparison to aw 1. Maybe as shown for vegetative microorganism the solutes can interact with membranes, e.g. inner spore membrane. FCM (flow cytometry) measurement data show a similar trend.